Faktor Yang Mempengaruhi Pelayanan Kesehatan Terhadap Kepuasan Pasien Rawat Inap Di RSUD DR. R.M. Djoelham Binjai Tahun 2022 - Erlindai Purba; Angelia Putriana; Afifah Roselini Pasaribu (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares with what he expects. The purpose of this study is to have a very strategic role in accelerating the improvement of public health status in providing health services. This research method uses quantitative research methods with a cross sectional approach. The population in this study were all inpatients at RSUD Dr. R.M Djoelham Binjai totaled 331 patients. The sample to be studied is 76 respondents. The sampling technique in this study used the accidental sampling technique. Data were analyzed by performing chi-square analysis test. The conclusion of this study is based on hypothesis testing using quantitative methods based on simple linear regression test equipment (F test) it was found that the significance value was 0.0053 or less than 0.05, therefore there was a positive influence between the health service variables (X). Caused by several factors, among others, namely physical evidence (Tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (emphaty) to the satisfaction of inpatients (Y). It is hoped that services that have received a satisfied response from patients will be maintained and improved by measuring the level of patient satisfaction on a regular basis so that they can monitor and maintain the quality of health services.